Longitudinal associations between use and co-use of cigars and cigarettes: A pooled analysis of three adolescent cohorts. (1st August 2019) - Kong, Grace; Mayer, Margaret E.; Barrington-Trimis, Jessica L.; McConnell, Rob; Leventhal, Adam M.; Krishnan-Sarin, Suchitra
Highlights: 3 youth cohort studies assessed the transition of cigar use to cigarette/dual use. Cigar use was associated with 2-fold increase in odds of subsequent cigarette use. Cigar use was associated with 3-fold increase in odds of subsequent dual use. Abstract: Introduction: Patterns of adolescent tobacco product use are evolving rapidly and need examination. We assessed whether ever use of cigars (i.e., lifetime use) was related to an increased risk of subsequent cigarette initiation and dual use of cigars and cigarettes. Methods: Leveraging data from three prospective cohort studies of adolescents (n = 6258), we assessed the odds of initiating cigarettes at one-year follow-up among ever cigar users at baseline, relative to never cigar users, after adjusting for demographics and e-cigarette use. We also assessed patterns of transition between exclusive use of cigars, exclusive use of cigarettes, and dual use of both cigars and cigarettes between baseline and follow-up and whether these associations differed by e-cigarette use. Results: Among never cigarette smokers (n = 4876; 79.3% of the total sample), 3.4% reported ever cigar use by baseline. Ever cigar use by baseline was associated with higher likelihood of initiating cigarettes by follow-up (31.3%) relative to never cigar use at baseline (8.4%; adjusted odds ratio = 2.26, 95% confidence interval: 1.52, 3.35). Effect estimates were stronger if e-cigarette was used by baseline. Furthermore, exclusive ever cigar use by baseline was associated with a 2-4-fold increase in the odds of transition to exclusive cigar, exclusive cigarette, and dual use at follow-up relative to non-users of either product by baseline. Conclusions: Comprehensive tobacco regulations and early prevention efforts focused on reducing youth appeal of cigars may be warranted, as cigar use may place youth at risk for subsequent cigarette use as well as dual use of cigars and cigarettes.